The teaching poetry style of Ahmadi's book, for example - Wali, ِِAsst.L. Nechirwan Jassim (Sulaimani Journal for Humanities, 2024)
Sheikh Marfi Node has worked in more than one religious and cultural field. Sheikh Marfi himself was a religious figure and graduated from the Hujra and Mosque. One of the areas in which Sheikh Marfi Nude has focused his efforts is the establishment of an Arabic-Kurdish dictionary, which is taught in the early stages of jurisprudence and used to learn Arabic. Most of Sheikh Node's works and writings are in Arabic, which was the common language of writing in his day. Among his books, Ahmadi's is the only one in Kurdish, written in the form of poetry and written to teach Arabic. Despite more than two centuries of writing the book and writing dozens of different books to teach Arabic, but still this book has scientific value and educational value and is relied upon in its field and is a gateway for students to learn Arabic Research and investigate.
Keywords: Teaching Poems; Sheikh Marfi Node; Ahmadi Book